Integrate some of the 21st century skills into the curricula of the second category of basic education from the point of view of teachers and specialist directories - Yousef, Asef; Jourea , Rehab (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
The research aims to identify the 21st century skills that must be provided in the curricula of the second category of basic education from the point of view of teachers and specialist directories, and to define the degree to which these skills need to be continued in secondary school curricula, and the effect of the variables )the function, the nature of the course material, and the scientific qualification). In order to achieve the objectives of the research, the descriptive method was used by designing a questionnaire consisting of 5 axes and 47 phrases representing 5 main skills of 21st century skills, it’s (the critical thinking and problem solving, the creativity and Innovation, the dialogue and communication, information technology culture, the life and work.). The sample consisted of (289) teachers and (70) specialist directories. The most important results of the research: - All the skills of the 21st century included in the questionnaire were highly approved, and ranked as the following (the work and life, the investment of technology and information, the creativity and innovation, the critical thinking and problem solving, the dialogue and communication). - All of the major 21st century skills included in the questionnaire were highly appropriate to the continuation of these skills in secondary school curricula. - There are no statistically significant differences between the average responses of the members of the research sample with regard to the skills of the 21st century, which should be available in the curriculum of the second category of basic education according to variation in the nature of the work of the sample members (teacher, directory),and in the scientific qualification. - There were statistically significant differences between the average of responses scores of the members of the research sample in relation to the skills of the 21st century, which should be available in the curricula of the second category of basic education according to the variable nature of the subject in favor of the scientific subjects for the skills of creativity and innovation, the investment of technology, Dialogue and communication, whereas there were no differences for the other skills.